Wasritano (Wayang Sri Tanjung Surowono) sebagai Alternatif Pendidikan Karakter Pemuda dari Relief Candi Surowono - Fajar Santoso (UIN Imam Bonjol Padang, 2024)
One of the criteria that can show the civilization of a nation can be seen from its cultural heritage. One of the form of cultural heritage is Surowono Temple that is located on Kediri Regency. The condition of Surowono Temple is not well maintained and have very few visitors become reason that makes the research about this temple is very important to do. Whereas, Surowono temple is not too far from Kampung Inggris that always crowd as a destination to learn English language. This research aims to (1) know the history background of Surowono Temple, (2) know the story and character value of Sri Tanjung’s relief, (3) implemented the story and character value of the relief to become Wayang Sri Tanjung as a form of Surowono Temple conservation. This research uses qualitative methods. The data obtained is the result from interview, direct observation, documentation, and literature study. This result of this research show that: first, Surowono Temple is a monument from Majapahit Kingdom as a place of King Hayam Wuruk’s uncle funeral called Bhre Wengker. Second, Sri Tanjung’s relief describing sadness and regret Sidapaksa after kill his wife, Sri Tanjung. Murder is happen because Sri Tanjung slandered has been seduced King Sulakrama. From that story, we can take the value of loyalty and trust to the spouse. Third, the character value inside Sri Tanjung’s relief on Surowono Temple will be implemented through interesting media of wayang as a form of Surowono Temple conservation to the visitors of Kampung Inggris, youth organization, or can be added into the school learning. Wayang Sri Tanjung will be featured in 4 stages which is accompanied by Kidung Sri Tanjung as a companion song and will be narrated into English Language and Indonesian Language as a form of Pare subdistrict locality.